The Double Alexander the Great? - Müller, Sabine (Amaltea. Revista de Mitocrítica, 2011)
On the basis of an ancient tradition on their visit to the captured royal family of the Persian great king, Hephaistion, the closest friend and confidant of Alexander the Great, was depicted in European art of the Renaissance and Baroque as his look-alike. The ancient background was Aristotle’s theories on friendship. During the 20th and 21st centuries the image of the doubled Alexander received further treatment. Hephaistion was shown as a mere shadow of Alexander and opportunist while Alexander was depicted as a true philosopher king and hero or as a person at odds with himself.